Earth abundant, non-toxic, 3D printed Cu2−xS with high thermoelectric figure of merit. Issue 44 (31st October 2019) - Burton, Matthew R.; Mehraban, Shahin; McGettrick, James; Watson, Trystan; Lavery, Nicholas P.; Carnie, Matthew J.
Abstract : Bulk non-toxic and Earth abundant Cu2− x S is pseudo-3D printed in a low-cost method yielding ZT values of up to 0.63. Abstract : The toxicity, earth abundance and manufacturing costs of thermoelectric materials are three leading reasons why thermoelectric generators are not used in wide scale applications. This is the first paper to tackle all three of these problems simultaneously. A pseudo-3D printing technique is combined with Cu2− x S based inks to yield bulk samples capable of being used in traditional architecture thermoelectric generators. These bulk samples are characterised over a wide temperature range in XPS, which reveals a curing temperature of 550 K yields pure Cu2− x S samples. The thermoelectric properties of these samples are tested over a wide temperature range, with a peak ZT of 0.63 ± 0.09 being recorded at 966 K. This work gives a significant advancement towards low cost highly efficient non-toxic thermoelectric generators. This work also provides the first route to print Cu2− x S, a material of much interest to the solar cell, catalysis and biosensor fields.